Velar Verbs and Verbal Classes in Catalan - Joaquim Viaplana (Universitat Autònoma de Barcelona, 2005)
There is in Catalan a set of verbs, the so-called «velar verbs», whose differential characteristic consists in presenting a velar segment between the root and the inflectional suffixes in certain morphosyntactic contexts. This velar segment has traditionally been considered as being part of the root in the contexts where it occurs, and has been made responsible for the typical allomorphic character of velar verbs. Under the assumption that regular verbs are only one-root verbs, velar verbs have been treated as irregular verbs. Nevertheless, neither the phonic character of the velar segment nor the marginal character of velar verbs is clear. The aim of this paper is to present a different account of velar verbs on the basis of the inflectional morphological character of the velar segment. The work is split into two parts. The first one focuses on standard Catalan, and tries to show that in this variety velar verbs are better treated as regular verbs. The second one focuses on other Catalan varieties, and aims to exhibit the incoherence implied in the traditional treatment of velar verbs in the context of the Catalan language as a whole. The discussion is mainly developed on morphological grounds, halfway between theory and description.